Rural Electrification and Fertility – Evidence from Côte d'Ivoire - Jörg Peters; Colin Vance (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2010)
Using household-level survey data from Côte d'Ivoire, this paper investigates the determinants of fertility with a particular focus on the effect of electrification. Based on count data regression models, our analysis suggests a highly significant relationship between fertility and electricity, but one that is only revealed when the model distinguishes between rural and urban areas. Specifically, we find a positive association between electricity and fertility for urban households, contrasted by a negative relationship for rural households. This dichotomy is suggested to reflect the influences of electricity in facilitating child care, off set by its modernizing impacts through the provision of information.
Keywords: O12; O33; J13; 330; Rural development; energy access; demography; count data; Elektrizitätspolitik; Wirkungsanalyse; Ländlicher Raum; Fruchtbarkeit; Kinderbetreuung; Elfenbeinküste